A flame-retardant solid silicone composition and a method for producing the same
Patent Information
- Application Number
- CN202611246333.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-16
AI Technical Summary
[0004]本发明要解决的技术问题是:针对现有技术中,阻燃硅橡胶在制备和使用过程中,阻燃剂容易发生迁移流失,从而导致实际产品的阻燃性能随着产品的存放会逐渐下降的问题
本申请上述技术方案采用片状氢氧化铝与聚磷酸铵构成复配阻燃体系。片状氢氧化铝发挥双重阻燃作用:一方面,其在高温下发生吸热分解(约200-300℃开始脱水),释放水蒸气稀释可燃气体浓度,生成的氧化铝残渣作为隔热屏障覆盖于材料表面,与APP的膨胀成炭机制形成协同阻燃效应;另一方面,分散于硅橡胶基体中的片状氢氧化铝作为物理阻隔填料,通过“迷宫效应”延长APP分子的迁移路径。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of flame retardant materials technology. More specifically, it relates to a flame-retardant solid silicone composition and its preparation method. Background Technology
[0002] Silicone rubber is widely used in electronics, automotive, and aerospace industries as a sealing, shock-absorbing, and insulating material due to its excellent resistance to high and low temperatures, electrical insulation, and chemical stability. With increasingly stringent safety standards, many applications require silicone rubber materials to possess flame-retardant properties. Currently, the most direct and economical way to impart flame retardancy to silicone rubber is to add flame retardants during the mixing process, such as aluminum hydroxide, ammonium polyphosphate, and organophosphorus-nitrogen flame retardants.
[0003] However, the inventors gradually realized a common problem in actual production and application: the flame-retardant effect of flame-retardant solid silicone compositions prepared based on additive flame-retardant systems often decreases to varying degrees after long-term storage. Some products can achieve a flame-retardant rating of V-0 when they leave the factory, but after several months or even longer storage periods, the flame-retardant rating may drop to V-1 or even lower when tested again, or the self-extinguishing time may be significantly prolonged. This performance degradation phenomenon brings significant uncertainty to product quality control, distribution, and end-use. Summary of the Invention
[0004] The technical problem this invention aims to solve is that, in existing technologies, flame retardants in flame-retardant silicone rubber tend to migrate and leak during preparation and use, leading to a gradual decrease in the flame-retardant performance of the actual product as it is stored. Based on this challenge, this invention provides a flame-retardant solid silicone composition and its preparation method.
[0005] The purpose of this invention is to provide a flame-retardant solid silicone composition.
[0006] Another object of the present invention is to provide a method for preparing a flame-retardant solid silicone composition.
[0007] The above-mentioned objective of this invention is achieved through the following technical solution: A flame-retardant solid silicone composition comprising: Silicone rubber matrix; A compound flame retardant, wherein the compound flame retardant comprises flake aluminum hydroxide and ammonium polyphosphate; The flake aluminum hydroxide includes first aluminum hydroxide particles and second aluminum hydroxide particles; The first aluminum hydroxide particle has a D50 of 30-40 μm and an aspect ratio of 30-50; the second aluminum hydroxide particle has a D50 of 1-3 μm and an aspect ratio of 10-30. The mass ratio of the first aluminum hydroxide particles to the second aluminum hydroxide particles is 6-10:1.
[0008] The beneficial effects of the above technical solution are as follows: The above-mentioned technical solution of this application adopts a compound flame retardant system composed of flake aluminum hydroxide and ammonium polyphosphate. Flake aluminum hydroxide plays a dual flame retardant role: on the one hand, it undergoes endothermic decomposition at high temperature (dehydration begins at about 200-300℃), releasing water vapor to dilute the concentration of combustible gas, and the generated alumina residue acts as a heat insulation barrier covering the material surface, forming a synergistic flame retardant effect with the expansion and charring mechanism of APP; on the other hand, the flake aluminum hydroxide dispersed in the silicone rubber matrix acts as a physical barrier filler, extending the migration path of APP molecules through the "maze effect".
[0009] More importantly, the above technical solution uses two different sizes of sheet-like aluminum hydroxide in combination. Large-sized, high aspect ratio sheet-like particles (the first aluminum hydroxide particles) form the "skeleton" and "main beam" of the barrier network in the matrix. Their large size allows a single particle to cover a large two-dimensional planar area, establishing a basic layered stacking framework in the matrix with a relatively small number of particles. However, relying solely on large-sized sheet-like particles has limitations—the gaps between large particles are relatively large, and APP molecules can still migrate around the particles through these gap channels, forming a "leakage" path. Small-sized sheet-like particles (the second aluminum hydroxide particles) play the role of "filling" and "gap filling" here. The two form a multi-scale, multi-level layered stacking structure spanning from macro to micro in terms of spatial distribution. When APP molecules attempt to traverse this composite lamellar network, they not only need to bypass large-sized lamellar particles, but also need to change direction multiple times in the narrow channels between particles to bypass small-sized particles. This multi-level barrier effect of "skeleton blocking + gap sealing" makes the lengthening of the migration path far exceed the simple superposition of single-sized particles, but exhibits a geometric growth.
[0010] Furthermore, the mass ratio between the silicone rubber matrix and the compounded flame retardant is 8-10:1, and the mass ratio between the flake aluminum hydroxide and the ammonium polyphosphate is 3-5:1.
[0011] By optimizing the total ratio of silicone rubber matrix to compound flame retardant and the ratio of flake aluminum hydroxide to ammonium polyphosphate, the material is ensured to have excellent initial flame retardant performance and long-term flame retardant stability, while also taking into account the mechanical properties of the silicone composition, avoiding material embrittlement and strength loss caused by overfilling; the gradient flame retardant action temperature range enables the material to have flame retardant protection capabilities over a wide temperature range.
[0012] Furthermore, the surface of the first aluminum hydroxide particle is coated with a silane coupling agent, while the surface of the second aluminum hydroxide particle is not coated with a silane coupling agent.
[0013] The above technical solution employs differentiated surface treatment strategies for the two types of aluminum hydroxide particles. The first aluminum hydroxide particle is coated with a silane coupling agent. The alkoxy groups in the silane coupling agent molecule can undergo a condensation reaction with the hydroxyl groups on the ATH surface to form a covalently bonded graft layer. Simultaneously, the organic functional groups (such as alkenyl and methyl groups) at its other end have good compatibility with the silicone rubber molecular chain. The second aluminum hydroxide particle is not surface modified, retaining its polar hydroxyl characteristics, maintaining a high interfacial energy with the silicone rubber matrix. This thermodynamic instability drives its gradual migration and enrichment to the surface during mixing and vulcanization, forming a thin layer of inorganic particles on the material surface. The physical barrier effect of this thin layer can further inhibit the outward precipitation of APP molecules near the surface.
[0014] Furthermore, the silane coupling agent is selected from at least one of alkenyltrimethoxysilane, methyltrimethoxysilane, and dimethyldiethoxysilane.
[0015] A method for preparing a flame-retardant solid silicone composition, the specific preparation steps of which include: A compound flame retardant is obtained by mixing first aluminum hydroxide particles modified with silane coupling agent, second aluminum hydroxide particles without surface modification, and ammonium polyphosphate. The compounded flame retardant is mixed with the silicone rubber matrix to obtain a compound; The compound is vulcanized to obtain the flame-retardant solid silicone composition.
[0016] Furthermore, the modification step of the first aluminum hydroxide particles modified with the silane coupling agent surface includes: The first aluminum hydroxide particles were mixed with a silane coupling agent in an ethanol solution and stirred at 60-80℃ for 4-6 hours. After drying, the modified first aluminum hydroxide particles were obtained.
[0017] Furthermore, the mass ratio of the first aluminum hydroxide particles to the silane coupling agent is 20-25:1.
[0018] Furthermore, the mass ratio of the first aluminum hydroxide particles to the ethanol solution is 1:10-15; the mass fraction of the ethanol solution is 60-80%.
[0019] Furthermore, the mixing temperature is 80-85℃, and the mixing time is 20-30 minutes; and before the mixing, 8-10% by weight of the second aluminum hydroxide particles of microcrystalline wax is added to the silicone rubber matrix.
[0020] Furthermore, the vulcanization molding includes a first-stage vulcanization and a second-stage vulcanization. The first-stage vulcanization temperature is 160-190℃, the pressure is 5-12MPa, and the time is 5-20min. The second-stage vulcanization temperature is 180-230℃, the pressure is 10-20MPa, and the time is 3-4h.
[0021] The mixing temperature of 80-85℃ balances the softening and flowability of silicone rubber with the safety of preventing scorching, while the mixing time of 20-30 minutes ensures uniform dispersion and avoids over-processing degradation. The addition of microcrystalline wax not only improves the mixing and processing performance, but more importantly, it utilizes its precipitation behavior during the vulcanization process to synergistically promote the controllable migration and enrichment of small-particle ATH to the material surface, significantly improving the formation efficiency and density of the surface protective layer.
[0022] The two-stage vulcanization process fully matures the cross-linked network of silicone rubber while using high temperature to further drive the microcrystalline wax carrying small-particle ATH to the surface for secondary enrichment, compacting and densifying to form a continuous protective layer. At the same time, it completely removes low-molecular-weight volatiles, reducing the micropores formed inside the material due to the escape of volatiles. The elimination of these pores indirectly reduces the migration channels of APP molecules, improving the flame retardant stability after long-term storage from another dimension. Detailed Implementation
[0023] The present invention will be further illustrated below with reference to specific embodiments, but the embodiments do not limit the present invention in any way. Unless otherwise specified, the reagents, methods, and equipment used in the present invention are conventional reagents, methods, and equipment in this technical field.
[0024] Unless otherwise specified, all reagents and materials used in the following examples are commercially available.
[0025] Example 1 Modification of the first aluminum hydroxide particles: 100g of sheet-like aluminum hydroxide (first aluminum hydroxide particles) with a D50 of 35μm and a diameter-to-thickness ratio of 40 was added to 1000g of 70% ethanol solution with 5g of silane coupling agent (vinyltrimethoxysilane). The mixture was stirred at 70℃ for 5h. After the reaction was completed, the mixture was filtered, washed, and vacuum dried at 80℃ to constant weight to obtain the first aluminum hydroxide particles modified with silane coupling agent.
[0026] Preparation of compound flame retardants: 90g of the modified first aluminum hydroxide particles, 12g of the unmodified second aluminum hydroxide particles (D50 of 2μm and aspect ratio of 20), and 25g of ammonium polyphosphate were put into a high-speed mixer and mixed at 800r / min for 20min to obtain a compound flame retardant.
[0027] Mixing: Take 200g of silicone rubber matrix (methyl vinyl silicone rubber, vinyl content 0.15mol%) and put it into a two-roll mill. Control the roll temperature at 80℃, add the above-mentioned compound flame retardant, and add microcrystalline wax (i.e. 1.2g) of 10% by weight of the second aluminum hydroxide particles. Mix for 25 minutes until the material is uniform, and then sheet to obtain the compound rubber.
[0028] Vulcanization molding: The above-mentioned compound rubber was placed into a mold and placed on a flat vulcanizing machine for a first-stage vulcanization at a temperature of 175°C, a pressure of 8 MPa, and a time of 12 min. Then it was transferred to an oven for a second-stage vulcanization at a temperature of 200°C and a time of 3.5 h. After natural cooling, the flame-retardant solid silicone rubber composition was obtained.
[0029] Example 2 The difference between this embodiment and Embodiment 1 lies in the different proportions of each group and the different process parameters, as detailed below: (1) The first aluminum hydroxide particle has a D50 of 30 μm and a diameter-to-thickness ratio of 50, and the second aluminum hydroxide particle has a D50 of 1 μm and a diameter-to-thickness ratio of 30.
[0030] (2) Modification of the first aluminum hydroxide particles: Take 100g of the first aluminum hydroxide particles and add 4g of silane coupling agent (methyltrimethoxysilane) to 1500g of 60% ethanol solution. Stir and react at 60°C for 6h. The post-treatment is the same as in Example 1.
[0031] (3) Preparation of compound flame retardant: 120g of modified first aluminum hydroxide particles, 12g of unmodified second aluminum hydroxide particles (the mass ratio of the two is 10:1), and 44g of ammonium polyphosphate (the mass ratio of flake aluminum hydroxide to ammonium polyphosphate is 3:1).
[0032] (4) Mixing: 200g of silicone rubber matrix (methyl vinyl silicone rubber, vinyl content 0.12mol%), add the above-mentioned compound flame retardant (mass ratio of silicone rubber matrix to compound flame retardant is about 8.1:1), add microcrystalline wax (i.e. 0.96g) with 8% of the mass of the second aluminum hydroxide particles, mix at 85℃ for 20min.
[0033] (5) Vulcanization molding: the first stage vulcanization temperature is 160℃, the pressure is 12MPa, and the time is 20min; the second stage vulcanization temperature is 180℃ and the time is 4h.
[0034] Example 3 The difference between this embodiment and Embodiment 1 lies in the different proportions of each group and the different process parameters, as detailed below: (1) The first aluminum hydroxide particle has a D50 of 40 μm and a diameter-to-thickness ratio of 30, and the second aluminum hydroxide particle has a D50 of 3 μm and a diameter-to-thickness ratio of 10.
[0035] (2) Modification of the first aluminum hydroxide particles: Take 100g of the first aluminum hydroxide particles and add 4.8g of silane coupling agent (dimethyldiethoxysilane) to 1200g of 80% ethanol solution. Stir and react at 80°C for 4h. The post-treatment is the same as in Example 1.
[0036] (3) Preparation of compound flame retardant: 72g of modified first aluminum hydroxide particles, 12g of unmodified second aluminum hydroxide particles (the mass ratio of the two is 6:1), and 28g of ammonium polyphosphate (the mass ratio of flake aluminum hydroxide to ammonium polyphosphate is 5:1).
[0037] (4) Mixing: 200g of silicone rubber matrix (methyl vinyl silicone rubber, vinyl content 0.15mol%), add the above-mentioned compound flame retardant (mass ratio of silicone rubber matrix to compound flame retardant is about 9.3:1), add 9% of the mass of the second aluminum hydroxide particles of microcrystalline wax (i.e. 1.08g), the mixing temperature is 80℃, and the mixing time is 30min.
[0038] (5) Vulcanization molding: The first stage vulcanization temperature is 190℃, the pressure is 5MPa, and the time is 5min; the second stage vulcanization temperature is 230℃, the pressure is 15MPa, and the time is 3h.
[0039] Comparative Example 1 The difference between this comparative example and Example 1 is that only a single specification of flake aluminum hydroxide is used, that is, only the first aluminum hydroxide particles modified with silane coupling agent (D50 is 35μm, aspect ratio is 40) are used, and no second aluminum hydroxide particles are added. The total amount of the first aluminum hydroxide particles added is the same as the total amount of the two types of aluminum hydroxide added in Example 1 (102g). All other components and process parameters are the same as in Example 1.
[0040] Comparative Example 2 The difference between this comparative example and Example 1 is that only a single specification of flake aluminum hydroxide is used, that is, only unmodified second aluminum hydroxide particles (D50 is 2μm, aspect ratio is 20) are used, and the first aluminum hydroxide particles are not added. The total amount of the second aluminum hydroxide particles added is the same as the total amount of the two types of aluminum hydroxide added in Example 1 (102g). The remaining components and process parameters are consistent with those in Example 1.
[0041] Comparative Example 3 The difference between this comparative example and Example 1 is that the mass ratio of the first aluminum hydroxide particles to the second aluminum hydroxide particles is 3:1 (i.e., the first aluminum hydroxide particles are 76.5g and the second aluminum hydroxide particles are 25.5g), the total amount of the two types of particles added is the same as in Example 1 (102g), and the remaining components and process parameters are consistent with those in Example 1.
[0042] Comparative Example 4 The difference between this comparative example and Example 1 is that the mass ratio of the first aluminum hydroxide particles to the second aluminum hydroxide particles is 12:1 (i.e., the first aluminum hydroxide particles are 94.2g and the second aluminum hydroxide particles are 7.8g), the total amount of the two types of particles added is the same as in Example 1 (102g), and the remaining components and process parameters are consistent with those in Example 1.
[0043] Comparative Example 5 The difference between this comparative example and Example 1 is that ammonium polyphosphate is not added, that is, the compound flame retardant is composed only of flake aluminum hydroxide (90g of first aluminum hydroxide particles and 12g of second aluminum hydroxide particles), and the remaining components and process parameters are consistent with those of Example 1.
[0044] Comparative Example 6 The difference between this comparative example and Example 1 is that the first aluminum hydroxide particle has a D50 of 20 μm and an aspect ratio of 25, while the second aluminum hydroxide particle has a D50 of 5 μm and an aspect ratio of 15 (i.e., the particle size and aspect ratio of both particles are not within the range defined by this invention). The remaining components and process parameters are consistent with those of Example 1.
[0045] Performance tests were conducted on the products obtained in the examples and comparative examples. The relevant test methods and results are shown below: Initial flame retardant performance test: The vertical burning flame retardancy rating of each sample (strip size: 125mm×13mm×3mm) was tested according to UL 94 standard, and the flame retardancy rating of each sample in its initial state was recorded.
[0046] Flame retardant performance test after long-term storage: Each sample was placed in a constant temperature and humidity chamber (temperature 40℃, relative humidity 80%) for accelerated aging. After 28 days and 56 days of storage, the samples were taken out and the flame retardancy rating was tested again according to the UL 94 standard mentioned above.
[0047] Mechanical property testing: The tensile strength of each sample (dumbbell-shaped cutter, type 2) before long-term storage was tested according to GB / T 528-2009 standard.
[0048] The relevant test results are shown in Table 1; Table 1: Product Performance Test Results
[0049] As shown in Table 1, the initial flame retardant rating of the embodiments of the present invention remained at V-0 after long-term accelerated aging tests, indicating that the migration of the flame retardant was effectively suppressed and the flame retardant performance did not decrease significantly. Meanwhile, the mechanical properties of the embodiments are excellent, and the products possess good mechanical properties.
[0050] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.
Claims
1. A flame-retardant solid silicone composition, characterized in that, include: Silicone rubber matrix; A compound flame retardant, wherein the compound flame retardant comprises flake aluminum hydroxide and ammonium polyphosphate; The flake aluminum hydroxide includes first aluminum hydroxide particles and second aluminum hydroxide particles; The first aluminum hydroxide particle has a D50 of 30-40 μm and an aspect ratio of 30-50; the second aluminum hydroxide particle has a D50 of 1-3 μm and an aspect ratio of 10-30. The mass ratio of the first aluminum hydroxide particles to the second aluminum hydroxide particles is 6-10:
1.
2. The flame-retardant solid silicone composition according to claim 1, characterized in that, The mass ratio between the silicone rubber matrix and the compounded flame retardant is 8-10:1, and the mass ratio between the flake aluminum hydroxide and the ammonium polyphosphate is 3-5:
1.
3. The flame-retardant solid silicone composition according to claim 1, characterized in that, The surface of the first aluminum hydroxide particle is coated with a silane coupling agent, while the surface of the second aluminum hydroxide particle is not coated with a silane coupling agent.
4. The flame-retardant solid silicone composition according to claim 3, characterized in that, The silane coupling agent is selected from at least one of alkenyltrimethoxysilane, methyltrimethoxysilane, and dimethyldiethoxysilane.
5. A method for preparing a flame-retardant solid silicone composition as described in any one of claims 1-4, characterized in that, The specific preparation steps include: A compound flame retardant is obtained by mixing first aluminum hydroxide particles modified with silane coupling agent, second aluminum hydroxide particles without surface modification, and ammonium polyphosphate. The compounded flame retardant is mixed with the silicone rubber matrix to obtain a compound; The compound is vulcanized to obtain the flame-retardant solid silicone composition.
6. The method for preparing a flame-retardant solid silicone composition according to claim 5, characterized in that, The modification steps of the first aluminum hydroxide particles modified with the silane coupling agent include: The first aluminum hydroxide particles were mixed with a silane coupling agent in an ethanol solution and stirred at 60-80℃ for 4-6 hours. After drying, the modified first aluminum hydroxide particles were obtained.
7. The method for preparing a flame-retardant solid silicone composition according to claim 6, characterized in that, The mass ratio of the first aluminum hydroxide particles to the silane coupling agent is 20-25:
1.
8. The method for preparing a flame-retardant solid silicone composition according to claim 6, characterized in that, The mass ratio of the first aluminum hydroxide particles to the ethanol solution is 1:10-15; the mass fraction of the ethanol solution is 60-80%.
9. The method for preparing a flame-retardant solid silicone composition according to claim 5, characterized in that, The mixing temperature is 80-85℃ and the mixing time is 20-30 min; and before the mixing, 8-10% by weight of the second aluminum hydroxide particles of microcrystalline wax is added to the silicone rubber matrix.
10. The method for preparing a flame-retardant solid silicone composition according to claim 5, characterized in that, The vulcanization molding includes a first-stage vulcanization and a second-stage vulcanization. The first-stage vulcanization temperature is 160-190℃, the pressure is 5-12MPa, and the time is 5-20min. The second-stage vulcanization temperature is 180-230℃, the pressure is 10-20MPa, and the time is 3-4h.